Krisis kesihatan mental ibu tunggal B40 semasa pandemik COVID-19 : kajian kes di Pulau Pinang - Siti Marziah Zakaria,; Asila Nur Adlynd Mohd Shukry,; Wan Nurdiyana Wan Yusof,; Norehan Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 pandemic has a negative impact on the mental health and well-being of single mothers, especially from the B40 income group. The role of single mothers as sole breadwinner is challenged due to changes in their daily routines and work routines during the pandemic. Single mothers were also reported to have a lower quality of life and poor mental health than married mothers. This study explored the mental health crisis faced by single mothers in Penang during the COVID-19 pandemic. A focused group discussion (FGD) was conducted on ten (10) B40 single mothers from Balik Pulau, Penang who were selected based on inclusive criteria that have been set, using purposive sampling method. Thematic analysis technique was applied to identify themes of mental health crises experienced by B40 single mothers. Findings showed that single mothers from the B40 group experience sadness, depression, grief, anxiety, and loneliness, which may deteriorate their mental health. Financial and social support are fundamental for single mothers to elevate their mental health status after being affected by the pandemic. The findings of this study may help relevant parties to understand the mental health challenges faced by the single mothers. It can provide a guideline in designing appropriate intervention programs to enhance the well-being and quality of life of B40 single mothers.